The Joint Philosophical Program of Russell and Wittgenstein and Its Demise - Nikolay Milkov (Nordic Wittgenstein Review, 2013)
Between April and November 1912, Bertrand Russell and Ludwig Wittgenstein were engaged in a joint philosophical program. Wittgenstein’s meeting with Gottlob Frege in December 1912 led, however, to its dissolution—the joint program was abandoned. Section 1 of this paper outlines the key points of that program, identifying what Russell and Wittgenstein each contributed to it. The second section determines precisely those features of their collaborative work that Frege criticized. Finally, building upon the evidence developed in the first two sections, section 3 recasts along previously undeveloped lines Wittgensein’s logical–philosophical discoveries in the two years following his encounter with Frege in 1912. The paper concludes, in section 4, with an overview of the dramatic consequences the Frege–Wittgenstein critique had for Russell’s philosophical development.